2020
DOI: 10.1101/2020.04.03.023234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lack of Adipocyte Purinergic P2Y6Receptor Greatly Improves Whole Body Glucose Homeostasis

Abstract: Uridine diphosphate (UDP)-activated purinergic receptor P2Y 6 (P2Y 6 R) plays a crucial role in controlling energy balance through central mechanisms. However, P2Y 6 R's roles in peripheral tissues regulating energy and glucose homeostasis remain unexplored. Here, we report the surprising novel finding that adipocyte-specific deletion of P2Y 6 R protects mice from dietinduced obesity, improving glucose tolerance and insulin sensitivity with reduced systemic inflammation. These changes were associated with redu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In C2C12 cells, activation of P2Y 6 R purinergic receptors (P2Y 6 Rs) increased GLUT4 translocation to the cell membrane by enhancing AMPK signaling, thereby increasing glucose uptake [151]. Consistent with this observation, ablation of P2Y 6 R specifically in SKM impaired whole-body glucose homeostasis and insulin sensitivity [34]. Lack of P2Y 6 R signaling reduced insulin-mediated glucose uptake in SKM (Fig.…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclesupporting
confidence: 60%
See 3 more Smart Citations
“…In C2C12 cells, activation of P2Y 6 R purinergic receptors (P2Y 6 Rs) increased GLUT4 translocation to the cell membrane by enhancing AMPK signaling, thereby increasing glucose uptake [151]. Consistent with this observation, ablation of P2Y 6 R specifically in SKM impaired whole-body glucose homeostasis and insulin sensitivity [34]. Lack of P2Y 6 R signaling reduced insulin-mediated glucose uptake in SKM (Fig.…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclesupporting
confidence: 60%
“…Lack of P2Y 6 R signaling reduced insulin‐mediated glucose uptake in SKM (Fig. 3; Table 1) [34]. A recent in vivo study examined mice that expressed a Gq‐linked designer GPCR (Gq DREADD) selectively in SKM [35].…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the role of P2Y receptors in regulating obesity and its impact on liver steatosis and inflammation. Mice lacking P2Y 6 R selectively in adipocytes were protected from diet-induced obesity (without a significant change in food intake) and systemic inflammation ( 71 ). Reduced obesity in adipocyte-P2Y 6 R KO resulted in lower liver weight and hepatic steatosis ( 71 ).…”
Section: Purinergic Signaling In Liver Metabolic Disordersmentioning
confidence: 99%